Empowering learners: exploring teacher perceptions in motivating and fostering self-directed learning skills - Tebogo Siziba; Bernadette Geduld; Charlene Du Toit-Brits (Cogent Education)
In literature, the role of self-directed learning is highlighted to counteract poor academic performance and dropouts caused by low motivation to learn and inadequate learning strategies. This study used the self-determination theory as a framework to explore teachers’ perceptions of the effects of motivation on learners’ self-directed learning skills in township schools. This qualitative study, positioned in an interpretivist paradigm, engaged purposively and conveniently selected teachers to explore their perceptions of the role of motivation in learners’ self-directed development. Semi-structured, single face-to-face interviews with the ten participants facilitated data collection. Thematic, inductive analysis was employed. Findings revealed that many teachers have low expectations, blaming learner demotivation on insufficient parental involvement and contextual challenges. The motivation for self-directed learning is hindered in some teacher-and-student relationships. Demotivated teachers and their insufficient demonstration of self-directed learning skills emerged as a barrier to the fostering of self-directed learning skills and learner motivation. Recommendations are proposed for different stakeholders to enhance learners’ motivation and self-directed learning skills.